Digital Transformation of Cooperative Legal Entities in Indonesia - Sukardi, Didi; Hafizd, Jefik Zulfikar; Muamar, Afif; Hamamah, Fatin; Royani, Esti; Sobirov, Babur (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
Abstract: This article captures the implementation of cooperative legal entities that are still conventional toward digital transformation, considering significant changes in the world. This study aims to describe how to strengthen the role of cooperatives as a pillar of the Indonesian economy, the legal basis for digital transformation, and the digital transformation of legal entity cooperatives in Indonesia. The findings show that transforming the cooperative business model into a digital basis is necessary. Cooperatives can obtain a vast market share by using tools such as website companies, social media, marketplace, and paid online advertising. The legal basis for business transformation from conventional to electronic-based models already exists. Cooperative legal entities can conduct business activities by utilizing digital technology for various activities such as administration, marketing via internet media, advertising using third parties such as Facebook Ads or Google Ads, selling products through online stores, analyzing business trends in the community, building relationships with more parties through social media, member meetings using video call applications, and many more that can be utilized. With the G20 forum, opportunities to expand business to various countries need to be used optimally by cooperatives in Indonesia. Keywords: Digital, Legal Entities, and Cooperatives.